Subverting Mainstream Narratives in the Reagan Era Giving Power to the People - Donnelly, Ashley M. (Springer International Publishing, 2018)
Subverting Mainstream Narratives in the Reagan Era explores how artists, novelists, and directors were able to present narratives of strong dissent in popular culture during the Reagan Era. Using but subverting the tools of mainstream novels and films, these visionaries' works were featured alongside other books in major bookstores and promoted alongside blockbusters in movie theatres across the country. Ashley M. Donnelly discusses how the artists accomplished this, why it is so important, and how new artists can use these techniques in today's homogenous and mundane media.